Multi-Objective Optimization of Mn-Doped Tio2 Content for Wettability, Printability and Intermetallic Layer of Sac305 Pb-Free Solder Paste on a Cu Substrate - Kannachai Kanlayasiri; Tadashi Ariga (Journal of Advanced Manufacturing Systems, 2021)
Effects of Mn-doped TiO 2 nanoparticles on the wettability, printability and thickness of intermetallic layer of SAC30 on a Cu substrate were studied in this paper. Concentration of Mn-doped TiO 2 nanoparticles was varied from 0.05 wt.% to 1[Formula: see text]wt.%. The wettability was evaluated in terms of contact angle of solder on the copper substrate and the printability was measured from the volume ratio of printed solder on the copper substrate to volume of stencil opening. The experimental results showed that 0.10[Formula: see text]wt.% Mn-doped TiO 2 led to the lowest contact angle while the printability was decreased with the increase of the added nanoparticles and the thinnest intermetallic layer was found at 0.50[Formula: see text]wt.% Mn-doped TiO 2 nanoparticles. Mn-doped TiO 2 concentration was then optimized using a desirability function to find optimal values for the three responses. It was found that 0.07[Formula: see text]wt.% was the optimal concentration for the three metrics — wettability, printability and thickness of the intermetallic layer.
Keywords: Electronic Packaging and Soldering Technologies; Metal and Thin Film Mechanics; Injection Molding Process and Properties